Recommendations for Implementing Hepatitis C Virus Care in Homeless Shelters: The Stakeholder Perspective. Issue 5 (3rd March 2020) - Fokuo, J. Konadu; Masson, Carmen L.; Anderson, August; Powell, Jesse; Bush, Dylan; Ricco, Margaret; Zevin, Barry; Ayala, Claudia; Khalili, Mandana
Abstract : Compared with the general population, homeless individuals are at higher risk of hepatitis C infection (HCV) and may face unique barriers in receipt of HCV care. This study sought the perspectives of key stakeholders toward establishing a universal HCV screening, testing, and treatment protocol for individuals accessing homeless shelters. Four focus groups were conducted with homeless shelter staff, practice providers, and social service outreach workers (n = 27) in San Francisco, California, and Minneapolis, Minnesota. Focus groups evaluated key societal, system, and individual‐level facilitators and barriers to HCV testing and management. Interviews were transcribed and analyzed thematically. The societal‐level barriers identified were lack of insurance, high‐out‐of‐pocket expenses, restriction of access to HCV treatment due to active drug and/or alcohol use, and excessive paperwork required for HCV treatment authorization from payers. System‐level barriers included workforce constraints and limited health care infrastructure, HCV stigma, low knowledge of HCV treatment, and existing shelter policies. At the individual level, client barriers included competing priorities, behavioral health concerns, and health attitudes. Facilitators at the system level for HCV care service integration in the shelter setting included high acceptability and buy in, and linkage with social service providers. Conclusion: Despite societal, system, and individual‐level barriers identified with respect to the scale‐up of HCV services in homeless shelters, there was broad support from key stakeholders for increasing capacity for the provision of HCV services in shelter settings. Recommendations for the scale‐up of HCV services in homeless shelter settings are discussed. Abstract : This study sought the perspectives of key stakeholders toward establishing a universal HCV screening, testing, and treatment protocol for individuals accessing homeless shelters. Four focus groups were conducted with social service outreach workers, homeless shelter directors and staff, and practice providers in San Francisco, California, and Minneapolis, Minnesota. Recommendations for HCV care integration included shortest course of HCV therapy, designated HCV coordinator, integration of substance use and mental health services, advocacy for extended shelter stays for clients with HCV, and HCV education for staff and clients.